1994
DOI: 10.1007/bf00134624
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced alcohol yields in batch cultures of Clostridium acetobutylicum using a three-electrode potentiometric system with methyl viologen as electron carrier

Abstract: ARYBatch cultures of Closrridium acetobutylicum at controlled pH values of 5 and 5.5 were carried out in a three-electrode potentiometric system with methyl viologen (1 mM) as electron carrier. Although an irreversible loss of methyl viologen at the electrode surface was observed, a significant increase in alcohol yield was obtained. In comparison to control fermentation with or without methyl viologen addition, the butanol yield improvements were respectively of 7 or 51% at pH 5, and 56 or 467% at pH 5.5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Reductions in acid production and yield were observed. These results coincide with previously reported findings (Peguin et al, 1994). The effect of using different methyl viologen addition times was also studied and is discussed later.…”
Section: Ab Fermentation Under Various Conditionssupporting
confidence: 93%
See 1 more Smart Citation
“…Reductions in acid production and yield were observed. These results coincide with previously reported findings (Peguin et al, 1994). The effect of using different methyl viologen addition times was also studied and is discussed later.…”
Section: Ab Fermentation Under Various Conditionssupporting
confidence: 93%
“…This can be achieved by decreasing the agitation rate , increasing the H 2 partial pressure (Mollah and Stuckey, 1992;, or CO gassing (Datta and Zeikus, 1985;Meyer et al, 1986). In this study, an electron carrier, methyl viologen, was used to alter the electron flow (Kim and Kim, 1988;Peguin et al, 1994;Mutharasan, 1986, 1987). Methyl viologen was chosen because it satisfies a number of requirements as a good electron mediator (Allen and Bowen, 1985), and it can replace FdH 2 in all reactions in which this protein is involved.…”
Section: Ab Fermentation Under Various Conditionsmentioning
confidence: 99%
“…To our knowledge, the purely electrochemical reduction of organics to ethanol has not been described in literature. Bioelectrochemical reductions of organics to ethanol, however, have been described (Peguin et al 1994;Shin et al 2002;Steinbusch et al 2009). Recently, Steinbusch et al (2009) found that acetate could be reduced to ethanol by mixed cultures in presence of a redox mediator such as methyl viologen.…”
Section: Ethanolmentioning
confidence: 99%
“…Microbial electrolysis cells (MECs) have been used to produce gaseous electrofuels such as hydrogen and methane (9,32,38). Other bioelectrochemical systems (BESs) have produced ethanol and butanol (28,34). There is a growing interest in using such technologies to produce longer-chain hydrocarbon fuels and other higher-value products (23,28,30).…”
mentioning
confidence: 99%
“…Other bioelectrochemical systems (BESs) have produced ethanol and butanol (28,34). There is a growing interest in using such technologies to produce longer-chain hydrocarbon fuels and other higher-value products (23,28,30).…”
mentioning
confidence: 99%